Nurse-focused ethical solutions to problems in organ transplantation - Ertin, Hakan (Nursing ethics, 2010)
Technological developments in recent years have brought about a rapid increase in the number and variety of organ transplants, leading to problems in finding enough organs to meet the need. Organ transplantation has also become a particularly significant issue in medical ethics, especially regarding the question of how and from whom organs are procured. Many methods have been tried in order to solve these problems and discussed from an ethical perspective. This study investigates the Spanish, Belgian and Iranian approaches to solving the organ procurement problem. The Spanish model, which is based on persuading patients and their relatives, is ethically less problematic and is also an improved version of the model applied in Turkey. This study argues that an ideal solution can be found without disregarding ethical rules. In particular, nurses can contribute by helping to run the system more efficiently. The principal aim of this article is to demonstrate the contribution of nurses to solving the current organ procurement problem in Turkey and offer some reflections on what can be done to improve the efficiency of the system.